Retrospective analysis of the occurrence and distribution of radix entomolaris in mandibular first molars: A hospital-based study - K Naveen Kumar; L Krishna Prasada; S Karthika Raj (Wolters Kluwer Medknow Publications, 2020)
Aim: This study aimed to evaluate clinically the prevalence of radix entomolaris (RE) in mandibular first molars in Dakshina Kannada population. Materials and Methodology: Proper clinical records and soft copies of radiographs of patients who had reported to the department of conservative dentistry and endodontics in a private dental college and hospital in Dakshina Kannada to seek root canal treatment from January 2015 to July 2019 were collected for the study. The occurrence and distribution of RE revealed by periapical radiographs and clinical case records were analyzed, and the comparison of the occurrence between males and females, and between the right and left sides, was done. Statistical analysis was done using the Chi-square test and binary logistic regression test with a statistically significant level set at P ≤ 0.05. Results: Among 1093 treated mandibular first molars, 52 teeth were RE. There was a significant difference in the prevalence of RE between males and females, but there was no significant difference between right and left sides' occurrence. Conclusions: Clinicians must be familiar with RE and its variations to reduce endodontic failures caused by missing canal.